MODEL OF FUNCTIONING LOGISTICS FOR SUPPLY OF SPECIALISED VEHICLES IN CONTAINERS FROM NORTH AMERICAN COMPANIES TO UKRAINE - Pavlenko, O.; Muzylov, D.; Medvediev, Ye. (Municipal economy of cities. Series: «Economy science», 2024)
The article analyses the current state and prospects for developing logistics for supplying various types of cargo in international traffic to be transported in containers. It allowed us to formulate the purpose of the study in this development. This topic is relevant since the efficient organisation of containerised supply logistics can improve the functioning of transport systems. An effective way to reduce the cost of supplying a cargo unit is efficient resource use (railway stations, ports, warehouses, wagons, vehicles, containers). The study paid considerable attention to developing the relevant infrastructure, solving specific problems of efficient use of all types of resources, using digital technologies, and building reliable models of logistics supply systems. The article builds a structural model based on the principles of logistics interaction of possible participants in the supply process, representing the interaction of subsystems that significantly affect the quality of the relevant operations. We formed five schemes of interaction between logistics participants for supplying specialised vehicles in containers with the participation of automobile, railway, and sea transport and the relevant infrastructure. These schemes identify the main ports of departure in the United States (New York and Houston) and ports of destination in Europe (Klaipeda (Lithuania), Constanta (Romania)), and take into account the possibility of using road and rail transport resources in European countries and Ukraine. We developed a mathematical model of logistics functioning for the supply of specialised vehicles in containers from North American enterprises to Ukraine, which accounts for the specifics of sequential operations and the peculiarities of determining the performance indicators of each supply chain operation. The prospect of using these models is to build a simulation model of logistics for the supply of specialised vehicles in containers from North American companies to Ukraine, conduct simulations using a software environment, and determine the rational option under the established conditions.